2011
DOI: 10.1530/rep-10-0419
|View full text |Cite
|
Sign up to set email alerts
|

Expression and effect of resistin on bovine and rat granulosa cell steroidogenesis and proliferation

Abstract: Resistin, initially identified in adipose tissue and macrophages, was implicated in insulin resistance. Recently, its mRNA was found in hypothalamo-pituitary axis and rat testis, leading us to hypothesize that resistin may be expressed in ovary. In this study, we determined in rats and cows 1) the characterization of resistin in ovary by RT-PCR, immunoblotting, and immunohistochemistry and 2) the effects of recombinant resistin (10, 100, 333, and 667 ng/ml)GIGF1 (76 ng/ml) on steroidogenesis, proliferation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 73 publications
6
54
0
6
Order By: Relevance
“…The first indication that resistin was involved in the regulation of the female reproductive system may be the discovery that resistin was expressed in rat ovaries throughout the oestrous cycle and was elevated in animals with induced ovarian cysts (Jones et al 2009). Subsequent study demonstrated resistin expression in ovarian cells of bovine (Maillard et al 2011), pigs , humans (Niles et al 2012, Reverchon et al 2013b) and the vespertilionid bat (Singh et al 2015). We demonstrated that both gonadotropins and steroid hormones significantly stimulated, while insulin growth factor type 1 (IGF1) and a synthetic agonist of PPARg reduced resistin expression and secretion by cultured porcine ovarian follicles, indicating that ovarian resistin expression can be regulated by several factor (Rak-Mardyła & Drwal 2015.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The first indication that resistin was involved in the regulation of the female reproductive system may be the discovery that resistin was expressed in rat ovaries throughout the oestrous cycle and was elevated in animals with induced ovarian cysts (Jones et al 2009). Subsequent study demonstrated resistin expression in ovarian cells of bovine (Maillard et al 2011), pigs , humans (Niles et al 2012, Reverchon et al 2013b) and the vespertilionid bat (Singh et al 2015). We demonstrated that both gonadotropins and steroid hormones significantly stimulated, while insulin growth factor type 1 (IGF1) and a synthetic agonist of PPARg reduced resistin expression and secretion by cultured porcine ovarian follicles, indicating that ovarian resistin expression can be regulated by several factor (Rak-Mardyła & Drwal 2015.…”
Section: Introductionmentioning
confidence: 76%
“…We demonstrated that both gonadotropins and steroid hormones significantly stimulated, while insulin growth factor type 1 (IGF1) and a synthetic agonist of PPARg reduced resistin expression and secretion by cultured porcine ovarian follicles, indicating that ovarian resistin expression can be regulated by several factor (Rak-Mardyła & Drwal 2015. Moreover, resistin ovarian expression is a species difference, with both granulosa and thecal cell expression in the cow, but only thecal cell expression in the rat (Maillard et al 2011). These species differences likely account for the differences in steroidogenesis observed.…”
Section: Introductionmentioning
confidence: 97%
“…Resistin is also present in the bovine ovaries (Table 1). Furthermore, human recombinant resistin decreases basal but not IGF-I-induced progesterone and oestradiol production by the bovine granulosa cells (Maillard et al, 2011). Spicer et al (2011), have also observed that resistin preferentially inhibited steroidogenesis in the granulosa cells from small follicles and inhibited proliferation of the granulosa cells from large follicles, suggesting that the ovarian response to resistin is altered during follicular development.…”
Section: Metabolic Hormonesmentioning
confidence: 84%
“…Certains variants et haplotypes identifiés sont associés à des tailles de portées plus grandes, un plus petit nombre de porcelets mort-nés et momifiés, et un intervalle sevrage-oestrus plus court [31]. La résistine est présente dans le liquide folliculaire, l'ovocyte, les cellules de la thèque et le corps jaune chez la rate et la vache [32]. Contrairement à la rate, elle est retrouvée dans les cellules de la granulosa production des stéroïdes par les cellules de la thèque en réduisant l'expression des récepteurs de la LH et des enzymes CYP11a1 (cytochrome P450, famille 11, sous-famille a, polypeptide 1) et CYP17a1 (cytochrome P450, famille 17, sous-famille a, polypeptide 1) [28].…”
Section: Rôle De L'adiponectine Et De La Résistine Au Niveau Des Gonadesunclassified
“…Dans les cellules de thèques humaines en culture, la résistine augmente l'expression de la 17-α-hydroxylase en présence de forskoline et/ou de forskoline + insuline, suggérant un rôle de la résistine dans la production d'androgènes [33]. Chez la vache et la rate, la résistine module différemment la steroïdogenèse et la prolifération des cellules de la granulosa en réponse à l'IGF-1, suggérant un effet dépendant de l'espèce [32].…”
Section: Ovaire Folliculeunclassified